2019
DOI: 10.21608/asnj.2019.56975
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Performance Regarding Care Of Chest Trauma Patients at Trauma Emergency Unit

Abstract: Background:The nurse is involved with the care of the trauma patient from arrival in the emergency department to follow-up in the trauma clinic. Chest injuries can be penetrating or the blunt type, depending on the nature and severity of the causative impact. The aim of this study was to assess nurses' performance regarding care of Chest Trauma patients at Trauma Emergency Unit. Design: Descriptive research designs were utilized in this study. Setting: This study was carried out in the emergency trauma unit at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Sometimes, the members of one team may follow other guidelines. A plethora of evidence indicates the importance of guidelines in organizing health care services and the quality of the outcomes 29,30 . For example, Al-Gabri et al (2020) conducted a study to evaluate the influence of unified CTM guidelines on EHPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, the members of one team may follow other guidelines. A plethora of evidence indicates the importance of guidelines in organizing health care services and the quality of the outcomes 29,30 . For example, Al-Gabri et al (2020) conducted a study to evaluate the influence of unified CTM guidelines on EHPs.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of evidence indicates the importance of guidelines in organizing health care services and the quality of the outcomes. 29,30 For example, Al-Gabri et al (2020) conducted a study to evaluate the influence of unified CTM guidelines on EHPs. They reported that unified guidelines for CTM would reduce psychological stress, anxiety, and negative attitudes toward EHP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the insertion and care of chest tubes demand a high level of expertise and skill to mitigate potential risks to the respiratory system. 3,4 Also known as intercostal catheters, chest tubes are pliable plastic tubes utilized for evacuating air (Pneumothorax), fluid (pleural effusion), blood, or purulent material (empyema) from the mediastinal cavity or pleural space. [5][6][7] Typically, these tubes remain in place post-thoracic or cardiac surgery until the output decreases to less than 150 ml in 24 hours, and any air leaks are resolved.…”
Section: Introductionmentioning
confidence: 99%